Drowning is fast, silent, and preventable: a Texas example of research in action - Stewart R. Williams; Emily A. Dow; Molly B. Johnson (BMC, 2023)
Abstract Drowning is a major public health issue internationally. In August 2022, a report was released by members of the Central Texas Drowning Prevention Action Team that provided data on drowning fatalities in Texas between 2006 and 2020 and offered recommendations for drowning prevention actions. The information in the Texas drowning report is an important contribution to the field of injury prevention. The aim of this editorial is to allow the information in the report to be available to a wider audience and potentially used as a model for other states.